Journalists' perceptions on determinants of corruption news framing / Kamaldeen Arikewuyo Ahmed and Rasaq Muhammed Adisa - Ahmed, Kamaldeen Arikewuyo; Adisa, Rasaq Muhammed (2018)
The pervasiveness of corruption frames in Nigerian newspapers has called concern for studies on how people interpret, respond and evaluate corruption issues. However, attention has not been directed to the forces behind corruption frames in Nigerian newspapers. As such, this study explored journalists' perceptions of organizational and extra media forces on corruption frames in Nigerian newspapers consequent upon the 2016 public officers' arrests and trials on corrupt conducts. A total of 6 print registered correspondents were generated using purposive sampling in a population 27 correspondents to national newspapers found in Kwara State. Using a qualitative in-depth interview, Nvivo (10) software was used to analyze the interview responses in a thematic way. Findings revealed that ownership and economic pressures at the organizational level, and political influence and public relations at the extra media level are forces that shape and sieve corruption stories in Nigerian newspapers. Therefore, prompt payment for journalists at the organizational level and their protection from extra-media forces in their professional callings are recommended for objective corruption coverage. While this study explored the forces behind corruption frames in Nigerian newspapers, future research can attempt to explain why such forces.